Radiotherapy setup displacements in breast cancer patients: 3D surface imaging experience - Sá, Ana Cravo (2018)
Aim - In this study, we intend to compare two different setup procedures for female breast cancer patients. Background - Imaging in radiotherapy provides a precise localization of a tumour, increasing the accuracy of the treatment delivery in breast cancer. Materials and methods - Twenty breast cancer patients who underwent whole breast radiotherapy (WBRT) were selected for this study. Patients were divided into two groups of ten. Group one (G1) was positioned by tattoos and then the patient positioning was adjusted with the aid of AlignRT (Vision RT, London, UK). In group two (G2), patients were positioned only by tattoos. For both groups, the first 15 fractions were analyzed, a daily kilovoltage (kV) cone beam computed tomography (CBCT) image was made and then the rotational and translational displacements and, posteriorly, the systematic (Σ) and random (σ) errors were analyzed. Results - The comparison of CBCT displacements for the two groups showed a statistically significant difference in the translational left-right (LR) direction (ρ = 0.03), considering that the procedure with AlignRT system has smaller lateral displacements. The results of systematic (Σ) and random (σ) errors showed that for translational displacements the group positioned only by tattoos (G2) demonstrated higher values of errors when compared with the group positioned with the aid of AlignRT (G1). Conclusions - AlignRT could help the positioning of breast cancer patients; however, it should be used with another imaging method.